A bamboo hard carbon material and preparation method thereof

By adding specific compounds and plasma to the bamboo powder modification process, the problems of low specific capacity and short service life of sodium ion batteries are solved, the electrochemical performance and cycle stability of the battery are improved, and efficient sodium ion storage is achieved and release.

CN118908185BActive Publication Date: 2024-12-17SHAANXI PUSTAR ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411414783.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-17
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The problems of low specific capacity of sodium ion batteries, low initial Coulomb efficiency, low rate performance and short service life.

Method used

By adding N-hydroxysuccinimide, 2,5-furandimethyl alcohol and ethylenediamine in the bamboo powder modification process and undergoing plasma treatment, the charge distribution and chemical structure of the bamboo powder surface are changed, and the conductivity and interface are improved. Compatibility, forming a dense oxide layer and a nitride layer, promoting the intercalation and removal of sodium ions.

Benefits of technology

It significantly improves the specific capacity, initial Coulomb efficiency and rate performance of the ion battery, extends the service life of the battery, reduces performance attenuation, and reduces the generation of waste liquid and waste gas, meeting the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908185B_ABST
    Figure CN118908185B_ABST
Patent Text Reader

Abstract

The invention discloses a bamboo hard carbon material, comprising the following components in parts by weight: 65-70 parts of bamboo powder, 6-8 parts of phosphoric acid, 5-7 parts of ethylenediamine, 4-6 parts of N-hydroxysuccinimide, 3-6 parts of 2,5-furan dimethanol, and 80-90 parts of deionized water. The bamboo hard carbon material is prepared by the following method: bamboo is pre-treated and carbonized, ball-milled to obtain 500-mesh bamboo powder, then mixed with phosphoric acid, ethylenediamine, N-hydroxysuccinimide, 2,5-furan dimethanol, deionized, dried, filtered to obtain modified bamboo powder, and then the modified bamboo powder is carbonized at high temperature and plasma treated to obtain the bamboo hard carbon material. The bamboo hard carbon material prepared by the present invention can be used as a negative electrode material of an ion battery, which can effectively improve the specific capacity, initial coulomb efficiency, and rate performance of the ion battery, and enhance its cycle stability, prolong service life, and the production process is simple and easy to promote.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion batteries, and in particular to a bamboo hard carbon material and a preparation method thereof. Background Art

[0002] With the development of new energy technologies, ion battery technology has shown an unprecedented development trend. Lithium-ion batteries are the preferred batteries for new energy vehicles. With the accelerated development of new energy technologies such as new energy vehicles, lithium resource consumption is also increasing, resulting in rising prices for lithium raw materials. Sodium has similar physical and chemical properties to lithium, is abundant in reserves and inexpensive, so as an important next-generation energy storage device, sodium-ion batteries are receiving increasing attention.

[0003] Sodium-ion batteries are still in their infancy, and the negative electrode materials used in sodium-ion batteries are different from those used in lithium-ion batteries. Graphite, as a typical carbon-based negative electrode material for lithium-ion batteries, has relatively good electrochemical properties in lithium-ion batteries. However, when graphite is used as a negative electrode material for sodium-ion batteries, the large radius of sodium ions does not match the distance between graphite layers, and a stable intercalation compound cannot be formed, showing poor sodium storage behavior, which results in graphite being unable to be used as a negative electrode material for sodium-ion batteries.

[0004] Hard carbon has a complex microcrystalline structure, is abundant in resources and low in cost. It is currently the main negative electrode material used in sodium-ion batteries. Hard carbon material is an amorphous, difficult-to-graphitize carbon material, generally made from high-molecular polymers or biomass precursors through high-temperature cracking. Currently, the precursors for preparing hard carbon materials mainly include resins, mineral resources and biomass, among which biomass is the mainstream. Biomass precursors mainly include coconut shells, straw, starch, lignin, bamboo, etc.

[0005] Bamboo is a fast-growing herb with fast growth rate and strong carbon fixation ability. It is an ideal precursor of biomass hard carbon negative electrode material. As a new type of negative electrode material, hard carbon has relatively high lithium and sodium storage capacity and is a new generation of negative electrode material with great potential. However, hard carbon negative electrode materials still have problems such as low specific capacity, low initial coulomb efficiency, low rate performance and short service life in the industrialization process, which affects the large-scale promotion and use of hard carbon negative electrode materials in the battery field.

[0006] Publication No. CN118515260A discloses a bamboo-based hard carbon negative electrode material and a preparation method thereof and an alkali metal battery, which are prepared by the following method: mixing bamboo powder raw material and alkali solution, and performing chemical pretreatment to obtain softened bamboo powder; mixing the softened bamboo powder and a crosslinking agent, and performing a carbonization to obtain a crosslinked bamboo powder; mixing the crosslinked bamboo powder and a benzene-based organic matter, and performing a secondary carbonization to obtain the bamboo-based hard carbon negative electrode material. The preparation method provided by the present invention has a simple process and is easy to control. It not only realizes the homogenization and crosslinking modification of bamboo powder, but also solves the problems of poor thermal stability of bamboo powder, structural melting and foaming, and improves the carbon yield; and the introduction of heteroatoms in the crosslinking reaction and the impregnation and crosslinking of benzene-based organic matter significantly improve the electrochemical performance of the high platform of bamboo-based hard carbon. The bamboo-based hard carbon negative electrode material prepared based on this method is expected to achieve large capacity and rapid storage at the same time, and obtain high first coulomb efficiency and excellent rate performance. Although this method can improve the first coulombic efficiency and excellent rate performance, the carbonization temperature in the present invention reaches 1600° C., the energy consumption is high, and the large-scale production cost is relatively high.

[0007] Publication No. CN117163939A discloses a hard carbon negative electrode material for bamboo-based sodium ion batteries and its preparation method and application. The preparation method comprises the following steps: sterilizing, fungal attack, calcining, and washing bamboo powder in sequence to obtain a hard carbon negative electrode material. The hard carbon negative electrode material comprises a micron-sized bamboo charcoal matrix and a nano-sized fungal-derived carbon. The bamboo charcoal matrix and the fungal-derived carbon are interconnected. The fungal-derived carbon is calcined and sintered by fungi growing in situ on the surface of the bamboo powder. The bamboo charcoal matrix is ​​calcined and sintered by the bamboo powder after fungal attack. The prepared bamboo-based sodium ion battery hard carbon negative electrode material has excellent electrochemical performance and cycle stability when applied as a sodium ion battery negative electrode. Although the sodium ion battery prepared by this method has excellent electrochemical performance and cycle stability, the preparation by this method requires fungal attack, the fungal attack time is long, and the calcination temperature reaches 1700°C, the energy consumption is high, and the large-scale production cost is high, which is not suitable for large-scale promotion and application.

[0008] Therefore, solving the problems of low specific capacity, low initial Coulombic efficiency, low rate performance, and short service life of sodium-ion batteries is a technical problem that needs to be urgently solved in the current sodium-ion battery industry. Summary of the invention

[0009] The object of the present invention is to provide a bamboo hard carbon material and a preparation method thereof, so as to solve the problems of low specific capacity, low initial Coulomb efficiency, low rate performance, short service life, etc. of sodium ion batteries mentioned in the above background technology.

[0010] To achieve the above object, the present invention provides the following technical solution: a method for preparing a bamboo hard carbon material, specifically comprising the following steps:

[0011] Step 1, bamboo pretreatment: cut fresh bamboo into 20-30 cm lengths, dry them under natural conditions for 15-20 days to make the moisture content of the bamboo reach 15-20%, then place the bamboo in an ultrasonic cleaner and ultrasonically clean it with deionized water for 35-40 minutes to remove stains on the bamboo surface, dry and crush the cleaned bamboo, and the frequency of the ultrasonic cleaner is 125-150 Hz.

[0012] Step 2, bamboo carbonization: Place the bamboo pretreated in step 1 in a carbonization furnace, heat it to 520-580°C at a heating rate of 4-6°C / min under a nitrogen atmosphere, keep it for 3.0-3.5h, then cool and ball-mill to obtain 500-mesh bamboo powder.

[0013] Step 3, weighing 65-70 parts by weight of the ball-milled bamboo powder, 6-8 parts by weight of phosphoric acid, 5-7 parts by weight of ethylenediamine, 4-6 parts by weight of N-hydroxysuccinimide, 3-6 parts by weight of 2,5-furan dimethanol, and 80-90 parts by weight of deionized water, placing them in a reaction kettle, keeping them warm at 120-150° C. for 12-15 hours, cooling and filtering, and then stirring and washing with ethanol and filtering, stirring and washing with deionized water, and then drying them in a dryer to obtain modified bamboo powder.

[0014] Step 4: Place the modified bamboo powder in a carbonization furnace, heat it to 500-520°C at a heating rate of 4-6°C / min under a nitrogen atmosphere, keep it for 1.0-1.2h, then heat it to 820-850°C at a heating rate of 4-6°C / min, keep it for 1.0-1.2h, and cool it to obtain carbonized bamboo powder.

[0015] Step 5: Placing the carbonized bamboo powder in a plasma device for plasma treatment for 5 to 6 minutes to obtain a bamboo hard carbon material.

[0016] As a preferred technical solution of the present invention, the particle size of the crushed bamboo is ≤2 mm.

[0017] As a preferred technical solution of the present invention, the rotation speed of the ball mill is 105-110 rpm, and the rotation speed of the reactor is 150-180 rpm.

[0018] As a preferred technical solution of the present invention, the ethanol concentration is 85-90%.

[0019] As a preferred technical solution of the present invention, the temperature of the drying machine is set to 65-70° C. and the drying time is 90-100 minutes.

[0020] As a preferred technical solution of the present invention, the charge density of the plasma equipment is 1300-1400C / cm 3 , gas flow rate is 1.7~1.8L / min, pressure is 110~120kPa, and temperature is 65~70℃.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. In the process of bamboo powder modification, N-hydroxysuccinimide and 2,5-furan dimethanol are added to the present invention. N-hydroxysuccinimide can provide an N source for bamboo powder, change the surface charge distribution of bamboo powder, and increase the surface active sites. N-hydroxysuccinimide improves the electrochemical properties of hard carbon materials by improving the conductivity of bamboo hard carbon materials and promoting the embedding and extraction of sodium ions or lithium ions, thereby improving the specific capacity of ion batteries. N-hydroxysuccinimide has a certain stability in chemical reactions, which helps to improve the stability of hard carbon materials during charge and discharge cycles, extend the service life of batteries, and reduce performance degradation. At the same time, N-hydroxysuccinimide can improve the interface compatibility between bamboo hard carbon materials and electrolytes, reduce interface resistance, and improve the initial coulomb efficiency and rate performance of batteries. 2,5-Furan dimethanol is a biomass-based furan derivative compound containing two alcohol hydroxyl functional groups. These hydroxyl functional groups can undergo esterification, etherification and other reactions with the active sites on the surface of bamboo charcoal powder, thereby introducing furan rings and hydroxyl functional groups on the surface of bamboo charcoal powder, promoting the interaction between bamboo powder and other substances, improving the electrochemical properties of bamboo hard carbon materials, and thereby increasing the specific capacity of ion batteries. The introduction of hydroxyl groups can improve the hydrophilicity and dispersibility of bamboo powder, making it easier to disperse in aqueous solution and mix with other substances. 2,5-Furan dimethanol, as a cross-linking agent, can promote the interaction between bamboo powder particles, forming a tighter network structure, improving mechanical strength and durability, and extending the service life of the battery.

[0023] 2. The present invention adds ethylenediamine, and the amino group (-NH2) in the ethylenediamine can react with functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of bamboo powder to form an amide bond, thereby introducing amino functional groups on the surface of bamboo powder, increasing the hydrophilicity and polarity of the surface of bamboo powder, improving its ability to interact with polar substances (such as water, acid, alkali, etc.), increasing the active sites on the surface of bamboo powder, and introducing N source into bamboo powder, thereby improving the electrochemical properties of ion batteries such as specific capacity and rate performance.

[0024] 3. The present invention treats the carbonized bamboo powder with plasma. The high-energy particles such as electrons and ions generated by the plasma equipment collide and react with the surface of the carbonized bamboo powder, change the chemical structure of the surface of the carbonized bamboo powder, form a dense oxide layer, a nitride layer, etc., improve the surface properties of the carbonized bamboo powder, and thus improve the electrochemical properties such as the specific capacity and rate performance of the ion battery. Plasma treatment can enhance the structural stability of the carbonized bamboo powder, so that it can better resist volume expansion and contraction during the insertion and removal of sodium ions or lithium ions, thereby extending the cycle life of the battery. At the same time, plasma treatment is a physical treatment method that does not require the use of a large amount of strong acid and alkali chemicals, reduces the generation of waste liquid and waste gas, meets the requirements of sustainable development, and is beneficial to environmental protection.

[0025] 4. In the carbonization process of the modified bamboo powder of the present invention, the temperature is first maintained at 500-520°C for 1.0-1.2h and then raised to 820-850°C and maintained for 1.0-1.2h for carbonization. Carbonization at a relatively low temperature of 500-520°C can form a dense carbide layer on the surface of the material, thereby improving the corrosion resistance and fatigue resistance of the material and extending the service life of the material. At the same time, high-temperature carbonization at 820-850°C can make carbon atoms more evenly distributed on the surface of the material to form a uniform carbonized layer, thereby obtaining a better carbonization effect and improving the overall performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a flow chart for preparing the bamboo hard carbon material of the present invention;

[0027] Figure 2 It is a line graph of the discharge specific capacity of the sodium ion battery of the present invention at different discharge cycle numbers. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention adds N-hydroxysuccinimide and 2,5-furan dimethanol in the bamboo powder modification process, wherein the N-hydroxysuccinimide can provide an N source for the bamboo powder, change the surface charge distribution of the bamboo powder, and increase the surface active sites; the N-hydroxysuccinimide improves the electrochemical performance of the hard carbon material by improving the conductivity of the bamboo hard carbon material, promoting the embedding and extraction of sodium ions or lithium ions, and further improves the specific capacity of the ion battery; the N-hydroxysuccinimide has a certain stability in the chemical reaction, which helps to improve the stability of the hard carbon material in the charge and discharge cycle process, prolong the service life of the battery, and reduce the performance attenuation; and the N-hydroxysuccinimide can improve the interface compatibility between the bamboo hard carbon material and the electrolyte, reduce the interface resistance, and improve the initial coulomb efficiency and rate performance of the battery. 2,5-Furan dimethanol is a biomass-based furan derivative compound containing two alcohol hydroxyl functional groups. These hydroxyl functional groups can undergo esterification, etherification and other reactions with the active sites on the surface of bamboo charcoal powder, thereby introducing furan rings and hydroxyl functional groups on the surface of bamboo charcoal powder, promoting the interaction between bamboo powder and other substances, improving the electrochemical properties of bamboo hard carbon materials, and thereby increasing the specific capacity of ion batteries. The introduction of hydroxyl groups can improve the hydrophilicity and dispersibility of bamboo powder, making it easier to disperse in aqueous solution and mix with other substances. 2,5-Furan dimethanol, as a cross-linking agent, can promote the interaction between bamboo powder particles, forming a tighter network structure, improving mechanical strength and durability, and extending the service life of the battery.

[0030] The present invention adds ethylenediamine, and the amino group (-NH2) in the ethylenediamine can react with functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of bamboo powder to form an amide bond, thereby introducing amino functional groups on the surface of bamboo powder, increasing the hydrophilicity and polarity of the surface of bamboo powder, improving its interaction ability with polar substances (such as water, acid, alkali, etc.), increasing the active sites on the surface of bamboo powder, and introducing an N source into the bamboo powder, thereby improving the electrochemical properties of the ion battery such as the specific capacity and rate performance.

[0031] The present invention performs plasma treatment on carbonized bamboo powder, and high-energy particles such as electrons and ions generated by the plasma equipment collide and react with the surface of the carbonized bamboo powder, change the chemical structure of the surface of the carbonized bamboo powder, form a dense oxide layer, a nitride layer, etc., improve the surface performance of the carbonized bamboo powder, and thus improve the electrochemical properties such as the specific capacity and rate performance of the ion battery. Plasma treatment can enhance the structural stability of the carbonized bamboo powder, so that it can better resist volume expansion and contraction during the insertion and removal of sodium ions or lithium ions, thereby extending the cycle life of the battery. At the same time, plasma treatment is a physical treatment method, which does not require the use of a large amount of strong acid and alkali and other chemical agents, reduces the generation of waste liquid and waste gas, meets the requirements of sustainable development, and is beneficial to environmental protection.

[0032] The raw materials used in the present invention are all commercially available raw materials.

[0033] Embodiment 1

[0034] A method for preparing a bamboo hard carbon material comprises the following steps:

[0035] Step 1, bamboo pretreatment: cut fresh bamboo into 20 cm lengths, dry them under natural conditions for 15 days to make the moisture content of the bamboo reach 20%, then place the bamboo in an ultrasonic cleaning machine for ultrasonic cleaning with deionized water for 35 minutes to remove stains on the bamboo surface, dry and crush the cleaned bamboo, the frequency of the ultrasonic cleaning machine is 150 Hz, and the particle size of the crushed bamboo is ≤2 mm.

[0036] Step 2, bamboo carbonization: Place the bamboo pretreated in step 1 in a carbonization furnace, heat it to 520°C at a heating rate of 4°C / min under a nitrogen atmosphere, keep it for 3.5 hours, then cool and ball mill to obtain 500-mesh bamboo powder, with a ball mill speed of 105 rpm.

[0037] Step 3, weigh 65 parts by weight of bamboo powder after ball milling, 6 parts by weight of phosphoric acid, 5 parts by weight of ethylenediamine, 4 parts by weight of N-hydroxysuccinimide, 3 parts by weight of 2,5-furan dimethanol, and 80 parts by weight of deionized water, place them in a reactor, keep them warm at 120° C. for 15 hours, cool and filter them, then use ethanol to stir, wash and filter them, stir, wash and filter them with deionized water, and then place them in a dryer to dry them to obtain modified bamboo powder. The speed of the reactor is 150 rpm, the temperature of the dryer is set to 65° C., the drying time is 100 min, and the ethanol concentration is 85%.

[0038] Step 4: Place the modified bamboo powder in a carbonization furnace, heat it to 500°C at a heating rate of 4°C / min under a nitrogen atmosphere and keep it for 1.2 hours, then heat it to 820°C at a heating rate of 4°C / min and keep it for 1.2 hours, and cool it to obtain carbonized bamboo powder.

[0039] Step 5: Placing the carbonized bamboo powder in a plasma device for plasma treatment for 5 minutes to obtain a bamboo hard carbon material. The charge density of the plasma device is 1400C / cm 3 , gas flow rate is 1.8L / min, pressure is 120kPa, and temperature is 70℃.

[0040] Embodiment 2

[0041] A method for preparing a bamboo hard carbon material comprises the following steps:

[0042] Step 1, bamboo pretreatment: cut fresh bamboo into 30cm lengths, dry them under natural conditions for 20 days to make the moisture content of the bamboo reach 15%, then place the bamboo in an ultrasonic cleaner and ultrasonically clean it with deionized water for 40 minutes to remove stains on the bamboo surface, dry and crush the cleaned bamboo, the frequency of the ultrasonic cleaner is 125Hz, and the particle size of the crushed bamboo is ≤2mm.

[0043] Step 2, bamboo carbonization: Place the bamboo pretreated in step 1 in a carbonization furnace, heat it to 580°C at a heating rate of 6°C / min under a nitrogen atmosphere, keep it for 3.0 hours, then cool and ball mill to obtain 500-mesh bamboo powder, with a ball mill speed of 110 rpm.

[0044] Step 3, weigh 70 parts by weight of the ball-milled bamboo powder, 8 parts by weight of phosphoric acid, 7 parts by weight of ethylenediamine, 6 parts by weight of N-hydroxysuccinimide, 6 parts by weight of 2,5-furan dimethanol, and 90 parts by weight of deionized water, place them in a reactor, keep them at 150° C. for 12 hours, cool and filter them, then use ethanol to stir, wash and filter them, stir, wash and filter them with deionized water, and then place them in a dryer to dry them to obtain modified bamboo powder. The speed of the reactor is 180 rpm, the temperature of the dryer is set to 70° C., the drying time is 90 min, and the ethanol concentration is 90%.

[0045] Step 4: Place the modified bamboo powder in a carbonization furnace, heat it to 520°C at a heating rate of 6°C / min under a nitrogen atmosphere and keep it for 1.0 h, then heat it to 850°C at a heating rate of 6°C / min and keep it for 1.0 h, and cool it to obtain carbonized bamboo powder.

[0046] Step 5: Placing the carbonized bamboo powder in a plasma device for plasma treatment for 6 minutes to obtain a bamboo hard carbon material. The charge density of the plasma device is 1300C / cm 3 , gas flow rate is 1.7L / min, pressure is 110kPa, and temperature is 65℃.

[0047] Embodiment 3

[0048] A method for preparing a bamboo hard carbon material comprises the following steps:

[0049] Step 1, bamboo pretreatment: cut fresh bamboo into 25cm lengths, dry them under natural conditions for 158 days to make the moisture content of the bamboo reach 18%, then place the bamboo in an ultrasonic cleaning machine for ultrasonic cleaning with deionized water for 37 minutes to remove stains on the bamboo surface, dry and crush the cleaned bamboo, the frequency of the ultrasonic cleaning machine is 135Hz, and the particle size of the crushed bamboo is ≤2mm.

[0050] Step 2, bamboo carbonization: Place the bamboo pretreated in step 1 in a carbonization furnace, heat it to 560°C at a heating rate of 5°C / min under a nitrogen atmosphere, keep it for 3.2 hours, then cool and ball mill to obtain 500-mesh bamboo powder. The speed of the ball mill is 108 rpm.

[0051] Step 3, weighing 68 parts by weight of bamboo powder after ball milling, 7 parts by weight of phosphoric acid, 6 parts by weight of ethylenediamine, 5 parts by weight of N-hydroxysuccinimide, 4 parts by weight of 2,5-furan dimethanol, and 85 parts by weight of deionized water, placing them in a reactor, keeping them warm at 130° C. for 13 hours, cooling and filtering, and then stirring and cleaning with ethanol and filtering. Stirring and cleaning with deionized water, filtering, and placing them in a dryer to dry to obtain modified bamboo powder, the speed of the reactor is 150-180 rpm, the temperature of the dryer is set to 68° C., the drying time is 95 min, and the ethanol concentration is 88%.

[0052] Step 4: Place the modified bamboo powder in a carbonization furnace, heat it to 510°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep it for 1.1 h, then heat it to 830°C at a heating rate of 5°C / min and keep it for 1.1 h, and cool it to obtain carbonized bamboo powder.

[0053] Step 5: Placing the carbonized bamboo powder in a plasma device for plasma treatment for 5 minutes to obtain a bamboo hard carbon material. The charge density of the plasma device is 1350C / cm 3 , gas flow rate is 1.7L / min, pressure is 115kPa, and temperature is 68℃.

[0054] Comparative Example 1:

[0055] The N-hydroxysuccinimide in Example 2 is removed, and the other method steps are the same as those in Example 2.

[0056] Comparative Example 2:

[0057] The 2,5-furan dimethanol in Example 2 is removed, and the other method steps are the same as those in Example 2.

[0058] Comparative Example 3:

[0059] The ethylenediamine in Example 2 is removed, and the other method steps are the same as those in Example 2.

[0060] Comparative Example 4:

[0061] The carbonized bamboo powder treated by plasma in step 5 of embodiment 2 is removed, and the other method steps are the same as those of embodiment 2.

[0062] Comparative Example 5:

[0063] The fourth step of Example 2 is modified as follows: placing the modified bamboo powder in a carbonization furnace, heating the temperature to 520° C. at a heating rate of 6° C. / min under a nitrogen atmosphere, and maintaining the temperature for 2.0 h, and cooling the furnace to obtain carbonized bamboo powder. The other steps are the same as those of Example 2.

[0064] Comparative Example 6:

[0065] The fourth step of Example 2 is modified as follows: placing the modified bamboo powder in a carbonization furnace, heating the temperature to 850° C. at a heating rate of 6° C. / min under a nitrogen atmosphere, and maintaining the temperature for 2.0 h, and cooling the furnace to obtain carbonized bamboo powder. The other steps are the same as those of Example 2.

[0066] The bamboo hard carbon material obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5 and 6 and carbon black and polyvinylidene fluoride were mixed, coated and dried in a mass ratio of 8:3:1 to obtain an electrode sheet. A CR2032 button battery shell was selected, and the negative electrode shell, spring sheet, gasket, metal sodium sheet, diaphragm, electrode sheet and positive electrode shell were assembled together into a sodium ion battery, and its electrochemical properties were tested at a current density of 0.5 A / g.

[0067] The sodium ion battery assembled with bamboo hard carbon material prepared in the embodiment and comparative example was tested for the first discharge specific capacity and the first coulombic efficiency. The results are shown in Table 1. The first discharge specific capacity and the first coulombic efficiency of the sodium ion battery prepared and assembled in the embodiment 1, 2, and 3 are both high. The first discharge specific capacity of the sodium ion battery prepared and assembled in the comparative example 1, 2, 3, and 4 is low. The first coulombic efficiency of the sodium ion battery prepared and assembled in the comparative example 1 is only 74.3%. N-hydroxysuccinimide improves the specific capacity of the ion battery by improving the conductivity of the bamboo hard carbon material and promoting the embedding and extraction of sodium ions or lithium ions. At the same time, N-hydroxysuccinimide can improve the interface compatibility between the bamboo hard carbon material and the electrolyte, reduce the interface resistance, and improve the initial coulombic efficiency of the battery. 2,5-Furan dimethanol contains two alcohol hydroxyl functional groups, which can react with the active sites on the surface of bamboo charcoal powder by esterification, etherification and other reactions, thereby introducing furan rings and hydroxyl functional groups on the surface of bamboo charcoal powder, promoting the interaction between bamboo powder and other substances, and improving the specific capacity of ion batteries. Ethylenediamine increases the active sites on the surface of bamboo powder and introduces N sources to bamboo powder, thereby improving the specific capacity of ion batteries. High-energy particles such as electrons and ions generated by plasma equipment collide and react with the surface of carbonized bamboo powder, changing the chemical structure of the surface of carbonized bamboo powder, forming a dense oxide layer, nitride layer, etc., improving the surface properties of carbonized bamboo powder, and thus improving the specific capacity of ion batteries.

[0068] The sodium ion batteries assembled with bamboo hard carbon materials prepared in Example 2 and Comparative Examples 1, 2, 4, 5 and 6 were subjected to discharge specific capacity tests. The first discharge specific capacities of Example 2 and Comparative Examples 1, 2, 4, 5 and 6 were 385.7, 297.6, 312.4, 326.4, 379.5 and 382.4 mAh / g, respectively. The discharge specific capacity of the sodium ion batteries varied under the conditions of 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1000 discharge times. Figure 2 As shown, with the increase of discharge times, the discharge specific capacity of the sodium ion battery shows a downward trend. The discharge specific capacity of the sodium ion battery in Example 2 decreases slowly. After 1000 discharges, its discharge specific capacity is 297.5 mAh / g, which decreases by 22.9%. The discharge specific capacities of Comparative Examples 1, 2, 4, 5 and 6 after 1000 discharges decrease by 92.1%, 67.8%, 70.4%, 44.5% and 43.3%, respectively. At the same current density of 0.5 A / g, Example 2 shows a higher discharge specific capacity. After 200 charge and discharges, the discharge specific capacity only decreases by 1.5%, which has better stability, and the battery has strong rate performance, high cycle stability and long service life.

[0069] Table 1: First discharge specific capacity and first coulombic efficiency of sodium ion batteries

[0070]

[0071] In summary, the bamboo hard carbon material prepared by the present invention can be used as the negative electrode material of the ion battery, which can effectively improve the specific capacity, initial coulomb efficiency, and rate performance of the ion battery, enhance the cycle stability of the ion battery, and extend its service life. The production process is simple and easy to promote.

[0072] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A method for preparing bamboo hard carbon material, It is characterized in that The specific steps include: Step 1, bamboo pretreatment: cut fresh bamboo into 20-30 cm lengths, dry them under natural conditions for 15-20 days, so that the moisture content of the bamboo reaches 15-20%, and then place the bamboo in an ultrasonic cleaning machine for ultrasonic cleaning with deionized water for 35-40 minutes to remove stains on the bamboo surface, and then dry and crush the cleaned bamboo; Step 2, bamboo carbonization: placing the bamboo pretreated in step 1 in a carbonization furnace, heating to 520-580°C at a heating rate of 4-6°C / min under a nitrogen atmosphere, maintaining for 3.0-3.5 hours, then cooling and ball milling to obtain 500-mesh bamboo powder; Step 3, weighing 65-70 parts by weight of the ball-milled bamboo powder, 6-8 parts by weight of phosphoric acid, 5-7 parts by weight of ethylenediamine, 4-6 parts by weight of N-hydroxysuccinimide, 3-6 parts by weight of 2,5-furan dimethanol, and 80-90 parts by weight of deionized water, placing them in a reaction kettle, keeping them warm at 120-150° C. for 12-15 hours, cooling and filtering, and then stirring and washing with ethanol and filtering, stirring and washing with deionized water, and then drying them in a dryer to obtain modified bamboo powder; Step 4, placing the modified bamboo powder in a carbonization furnace, heating the temperature to 500-520° C. at a heating rate of 4-6° C. / min under a nitrogen atmosphere, maintaining the temperature for 1.0-1.2 h, then heating the temperature to 820-850° C. at a heating rate of 4-6° C. / min, maintaining the temperature for 1.0-1.2 h, and cooling the temperature to obtain carbonized bamboo powder; Step 5: Placing the carbonized bamboo powder in a plasma device for plasma treatment for 5 to 6 minutes to obtain a bamboo hard carbon material.

2. A method for preparing a bamboo hard carbon material according to claim 1, It is characterized in that The frequency of the ultrasonic cleaning machine is 125-150Hz, and the particle size of the crushed bamboo is ≤2mm.

3. The method for preparing a bamboo hard carbon material according to claim 1, It is characterized in that The rotation speed of the ball mill is 105-110 rpm, and the rotation speed of the reactor is 150-180 rpm.

4. The method for preparing a bamboo hard carbon material according to claim 1, It is characterized in that The ethanol concentration is 85-90%.

5. The method for preparing a bamboo hard carbon material according to claim 1, It is characterized in that The drying machine temperature is set to 65-70°C and the drying time is 90-100 minutes.

6. The method for preparing a bamboo hard carbon material according to claim 1, It is characterized in that The charge density of plasma equipment is 1300~1400C / cm 3 , gas flow rate is 1.7~1.8L / min, pressure is 110~120kPa, and temperature is 65~70℃.

7. A bamboo hard carbon material, It is characterized in that The compound is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Cited By

  • Starch asphalt composite hard carbon material as well as preparation method and application thereof

    CN121790390A